Antología de textos jurídicos de Roma, edición de Xavier d’Ors, Akal Clásica 61/Clásicos Latinos, Madrid, 2001, 399 pp., ISBN 84-460-1472-6 (Minerva, 2019)
Review: Antología de textos jurídicos de Roma, edición de Xavier d’Ors, Akal Clásica 61/Clásicos Latinos, Madrid, 2001, 399 pp., ISBN 84-460-1472-6